The Role of Prophage ϕSa3 in the Adaption of Staphylococcus aureus ST398 Sublineages from Human to Animal Hosts - Habib Dastmalchi Saei; Jo-Ann McClure; Ayesha Kashif; Sidong Chen; John M. Conly; Kunyan Zhang (Antibiotics, 2024)
Staphylococcus aureus sequence type (ST) 398 is a lineage affecting both humans and livestock worldwide. However, the mechanisms underlying its clonal evolution are still not clearly elucidated. We applied whole-genome sequencing (WGS) typing to 45 S. aureus strains from China and Canada between 2005 and 2014, in order to gain insight into their evolutionary pathway. Based on WGS phylogenetic analysis, 42 isolates were assigned to the human-associated clade (I/II-GOI) and 3 isolates to livestock-associated clade (IIa). Phylogeny of ϕSa3 sequences revealed five phage groups (Groups 1–5), with Group 1 carrying ϕSa3-Group 1 (ϕSa3-G1), Group 2 carrying ϕSa3-G2, Group 3 carrying ϕSa3-G3, Group 4 carrying ϕSa3-G4 and Group 5 lacking ϕSa3. ϕSa3-G1 was only found in strains that accounted for the most ancestral human clade I, while ϕSa3-G2, ϕSa3-G3 and ϕSa3-G4 were found restricted to sublineages within clade II-GOI. Some isolates of clade II-GOI were also found to be ϕSa3-negative or resistant to methicillin which are unusual characteristics for human-adapted isolates. This study demonstrated a strong association between phylogenetic grouping and phage type, suggesting an important role of ϕSa3 prophage in the evolution of human-adapted ST398 subclones. In addition, our results suggest that this subclone slowly began to adapt to animal hosts by losing ϕSa3 and acquiring methicillin resistance, which was observed in some strains of human-associated clade II-GOI, an intermediate human to livestock transmission clade.